2011
DOI: 10.1111/j.1740-8709.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Early child growth: how do nutrition and infection interact?

Abstract: It is well known that the relationship between child nutrition and infection is bidirectional, i.e. frequent illness can impair nutritional status and poor nutrition can increase the risk of infection. What is less clear is whether infection reduces the effectiveness of nutrition interventions or, vice versa, whether malnutrition lessens the impact of infection control strategies. The objective of this paper is to review the evidence regarding this interaction between nutrition and infection with respect to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
211
2
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(234 citation statements)
references
References 42 publications
9
211
2
12
Order By: Relevance
“…Infections, particularly diarrheal and upper respiratory diseases, occur most frequently during the first 2-3 years of life when immunocompetence is impaired and when, at the same time, children are first being exposed to disease pathogens (Rodríguez et al 2011). Infection can suppress appetite and directly affect nutrient metabolism, leading to poor nutrient utilization (Bloss et al 2004;Dewey & Mayers 2011). Indeed, children with poor appetite showed the highest prevalence of wasting as indicated in our results.…”
Section: Discussionsupporting
confidence: 60%
“…Infections, particularly diarrheal and upper respiratory diseases, occur most frequently during the first 2-3 years of life when immunocompetence is impaired and when, at the same time, children are first being exposed to disease pathogens (Rodríguez et al 2011). Infection can suppress appetite and directly affect nutrient metabolism, leading to poor nutrient utilization (Bloss et al 2004;Dewey & Mayers 2011). Indeed, children with poor appetite showed the highest prevalence of wasting as indicated in our results.…”
Section: Discussionsupporting
confidence: 60%
“…The age of 2 years is the age at which infectious diseases such as diarrhea carry an extremely high risk of stunting. (23) Children without exclusive breastfeeding were more numerous in the group of cases than in the group of controls. This study is similar to a study in Ethiopia which showed that children with less than 6 months of breastfeeding had a greater risk of stunting than children with exclusive breastfeeding during the first 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Infectious disease may be the cause of decreased dietary intake. Low dietary intake, decrease in nutrients as a result of vomiting, diarrhea, malabsorption and fever of long duration may cause nutrient deficiencies, and consequently infant and child growth and immune system abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Various hypothesis has said that frequent infections may make nutritional interventions may not as effective. 3 Based on Riskesdas 2010 data the prevalence of malnutrition in infants in Indonesia is still very high at 17,9%. 4 Due to its place in the tropical region, Indonesia is endemic to various different infectious diseases.…”
Section: Introductionmentioning
confidence: 99%